Weak and strong convergence of an implicit iteration process for an asymptotically quasi-I-nonexpansive mapping in banach space - Mukhamedov, Farrukh; Saburov, Mansoor (Hindawi Publishing Corporation, 2010)
We prove the weak and strong convergence of the implicit iterative process to a common fixed point of an asymptotically quasi-I-nonexpansive mapping T and an asymptotically quasinonexpansive mapping I, defined on a nonempty closed convex subset of a Banach space.